Energy reliability-constrained method for the multi-objective optimization of a photovoltaic-wind hybrid system with battery storage. (1st August 2018) - Mazzeo, Domenico; Oliveti, Giuseppe; Baglivo, Cristina; Congedo, Paolo M.
Abstract: A multi-objective optimization method for the dimensioning of hybrid photovoltaic-wind-battery systems HPWBS characterized by high-energy reliability is proposed. The energy reliability-constrained (ERC) method permits choosing the most proper indicators combination to be constrained or optimized as a function of the specific application. The ERC method is applicable to grid-connected and stand-alone hybrid systems with and without storage battery, for residential as well as for other uses. The reliability indicators defined are: the photovoltaic-wind fraction, energy fraction required by the load satisfied by the HPWBS; the utilization factor, energy fraction produced sent to the load; the manufacturability that characterizes the energy produced sent to the load in relation to the nominal power of the system. The ERC method was employed for the multi-objective optimization of a grid-connected hybrid system with and without storage battery for the electric energy supply to an urban residential building in a Mediterranean climate. A parametric analysis, for different loads, by varying the photovoltaic and wind power and the battery storage capacity, was developed to evaluate the annual energy reliability in a dimensionless form of 450 system configurations. The results allowed obtaining empiric correlations to be used in the system design. Finally, the ERC method application allowed achieving optimal system configurations with greater reliability compared with those provided by the Pareto-front method. Graphical abstract: Image 1 Highlights: Energy reliability-constrained ERC method for the multi-objective optimization of aHPWBS. ERC method applied to a grid-connected HPWBS to supply a variable load in a Mediterranean climate. HPWBS was simulated under dynamic conditions by means of TRNSYS software. Analytic correlations for the system dimensioning are proposed. ERC method was compared with the Pareto-front method in the identification of the optimal system configurations.